INOVASI KURIKULUM DAN PEMBELAJARAN - P Prastyawan (LPPM Institut Agama Islam Al-Hikmah Tuban, 2011)
Problems in the field of education issues including the relevance of education, issues of education quality, effectiveness and efficiency problems, problems of limited capacity. With the innovations in education, especially in the areas of curriculum and learning, is expected to provide real solutions to problems that exist. Curriculum innovation and learning is an idea, an idea or specific actions in the field of curriculum and learning a new thought to solve the problems of education. Innovation is exists because of the perceived problems. Planning of learning is very important to help teachers and students in creating, arranging, and organizing learning events that allow learning to occur in order to achieve learning objectives